Exploring Intimate Partner Violence Before, During, and After Pregnancy in Bangladesh. Issue 7 (April 2021) - Islam, Md. Jahirul; Broidy, Lisa; Mazerolle, Paul; Baird, Kathleen; Mazumder, Nurunnahar
Intimate partner violence (IPV) against pregnant or postpartum women is known to have multiple detrimental effects on women and their children. Although results from past research suggest much continuity in trajectories of IPV, it is unclear whether pregnancy interrupts or augments these patterns. Little is known about how physical, sexual, and psychological IPV change and overlap throughout a woman's transition to parenthood. Relying on population-based data, this study examines the prevalence, co-occurring nature, and the changing patterns of physical, sexual, and psychological IPV before, during, and after pregnancy in Bangladesh. Cross-sectional survey data were collected between October 2015 and January 2016 in the Chandpur District of Bangladesh from 426 new mothers, aged 15 to 49 years, who were in the first 6 months postpartum. IPV was assessed with a validated set of survey items. The frequencies of different types of IPV victimization according to the period of occurrence were calculated separately and in a cumulative, co-occurring manner. The prevalence of physical IPV before, during, and after pregnancy was 52.8%, 35.2%, and 32.2%, respectively. The comparative figures for psychological IPV were 67.4%, 65%, and 60.8%, and for sexual IPV were 21.1%, 18.5%, and 15.5%, respectively. The results demonstrate a notable continuity in IPV victimization before, during, and after pregnancy. Psychological IPV is the only type to exhibit a significant reduction during and after pregnancy, compared with before pregnancy, but it commonly overlaps with physical IPV, which shows a significant change during pregnancy and little change in the postpartum period. At the same time, pregnancy and childbirth offer little protection against IPV for women in relationships characterized by psychological or sexual victimization, both of which commonly overlap with physical IPV. Results reinforce the need to conduct routine screening during pregnancy to identify women with a history of IPV and to offer necessary help and support.